Alternative Conceptions about Heat and Temperature among Upper Primary School Students: A Longitudinal Study - Uzma, (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The purpose of the present study was to identify various alternative conceptions about heat and temperature among upper primary school students as they moved to classes 6, 7 and 8 respectively. Thermal Concept Evaluation, a standardised questionnaire, was used on a sample of 300 upper primary school students. The results of a one-way repeated measures ANOVA revealed that there was a gradual decrease in alternative conceptions among students with the passage of time but they still persisted. The findings of this study imply that innovative and alternative teaching approaches should be adopted for preventing and remediating students’ alternative conceptions in Physics